Evaluation of filter media covered with spun fibres and containing thyme essential oil with antimicrobial properties - Salussoglia, Ana Isabela Pianowski (Environmental technology, 2022)
Inhalation of bioaerosols has been linked to many health problems. Filter media impregnated with antimicrobial material can provide effective removal and inactivation of bioaerosols. In this study, fibres were spun on a substrate by centrifugal spinning, obtaining filter media denoted 5THY and THY. Thyme essential oil was used as an antimicrobial agent. For 5THY, the thyme essential oil was added to the polyacrylonitrile (PAN) solution, while for THY, it was sprayed onto the medium after the fibres had been produced. The THY medium presented a higher collection efficiency, compared to the substrate or 5THY, with efficiencies of 99% for microparticles and 58% for nanoparticles. Using the plaque assay method, THY provided the highest reductions of the bacteria Escherichia coli and Staphylococcus aureus, with efficiency of 99.999%. The findings demonstrated that filter media covered with spun fibres and containing thyme essential oil provided excellent antimicrobial action and filtration performance